Environmental Self-Efficacy And Environmental Love Action Program Among Students: Hubungan Efikasi Diri Lingkungan Dan Program Aksi Cinta Lingkungan Siswa - Santika Rahayu Wiguna; Siti Nurbayani K; Acep Supriadi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Environmental degradation caused by unmanaged waste has become a critical issue affecting environmental quality and public health, particularly in urban areas. Specific Background: In response to waste accumulation around the Geger Kalong area, Daarut Tauhiid Boarding School Bandung implemented the Environmental Love Action Program as a structured school-based waste management and environmental behavior initiative. Knowledge Gap: Previous environmental education initiatives often emphasize cognitive understanding, while limited empirical evidence explains the role of psychological factors, particularly environmental self-efficacy, in structured environmental programs within Islamic boarding school contexts. Aims: This study examines the relationship between environmental self-efficacy and student involvement in the Environmental Love Action Program among female middle school students. Results: Using a quantitative correlational approach with 148 respondents, Pearson Product Moment analysis revealed a strong and statistically significant relationship between environmental self-efficacy and program involvement (r = 0.769, p < 0.01). Novelty: This study provides empirical evidence linking environmental self-efficacy to sustained participation in a faith-based environmental action program within a boarding school setting. Implications: The findings indicate that strengthening students’ confidence in their environmental capabilities is essential for sustaining environmentally responsible behavior and supporting long-term waste management practices in educational institutions. Highlights • Strong correlation identified between environmental self-efficacy and student participation• Environmental action program supported sustained environmentally responsible behavior• Psychological confidence associated with consistency in school-based environmental practices Keywords Environmental Self-Efficacy; Environmental Action Program; Waste Management Education; Sustainable Behavior; Islamic Boarding School